Peran Pelatihan Mental Dalam Meningkatkan Kepercayaan Diri Atlet Renang Sekolah Ragunan - juriana, juriana; Tahki, Kurnia (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2017)
Sport confidence is important psychology’s aspect for athletes to be successful in their performance. SMP/SMA Ragunan’ swimmers are junior talent athletes to accelerate in sport champion. This research discuss about the role of mental training in enhancing sport confidence of SMP/SMA Ragunan’s swimmers. This is a qualitative research with pre-experiment design. The result of this research showed that mental training have actively role in enhancing sport confidence of SMP/SMA Ragunan’s swimmers. Relaxation and visualization training plays the best role in enhancing sport confidence. Based on result of this research suggest that Ragunan’s swimmers have to continue mental training until they get positive effect in their performance. Besides, sport needs more sport psychologist in the future to give mental training and education programe in another kinds of sport.